Sustainable Engineering Innovations for Renewable Energy Systems: A Systematic Literature Review of Technologies, Performance, and Environmental Impacts - Deki Saputra; Mohammad Qais Rezvani (International Journal of Sustainable Engineering Innovations, 2026)
Background of study: The transition to sustainable energy is essential to mitigate climate change. While renewable sources like solar and wind are key to decarbonization, their adoption is hindered by performance intermittency. Current research is often fragmented by technology type, lacking an integrated framework that simultaneously addresses engineering innovations, technical performance, and environmental sustainability. Aims paper: This study aims to synthesize sustainable engineering innovations by integrating technological development with operational performance and environmental impact assessments. The scope is limited to 20 peer-reviewed articles from the Scopus database published between 2019 and 2025. Methods: The research follows a Systematic Literature Review (SLR) design and PRISMA 2020 guidelines. Data were analyzed using Biblioshiny for descriptive statistics and VOSviewer for thematic and network visualization Result: Findings show an annual scientific growth rate of 44.22%. Key innovations focus on hybrid energy systems, smart grids, and energy storage. Recent trends indicate a shift toward digitalization, IoT-based management, and environmentally optimized materials. Conclusion: Sustainable engineering innovations significantly enhance system efficiency and reliability. Although they reduce greenhouse gas emissions, environmental performance varies by technology. The study concludes that interdisciplinary, system-level approaches are vital for achieving global sustainability goals.